2015
DOI: 10.2527/jas.2015-9610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal dietary manganese and incubation temperature on hatchability, antioxidant status, and expression of heat shock proteins in chick embryos1

Abstract: To investigate whether supplementing manganese (Mn) to the maternal diet could reduce the deleterious effect of heat stress on the developing embryo, the hatchability, antioxidant status, and expression of heat shock proteins (HSP) were evaluated in chick embryos under normal and high incubation temperatures. A completely randomized design ( = 6) with 2 maternal dietary Mn treatments (unsupplemented control basal diet versus the basal diet + 120 mg Mn/kg as inorganic Mn) × 2 incubation temperatures (normal, 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The birds were subsequently killed; samples of their liver, kidney, and heart were taken; and a subsample was frozen at −20°C for the analyses of Fe content and catalase (cAT) and succinate dehydrogenase (sDH) activities and another sample was frozen in liquid N for CAT and SDH gene expression assays. The samples of the liver, kidney, and heart were homogenized with a tissue grinder (T 18 D S25; IKA Group, Staufen, Germany) in ice-cold 10% (wt/vol) physiological saline for 1 min and then treated with an ultrasonic wave cell grinder (JY92-11; Ningbo Scientz Biotechnology Co., Ltd., Ningbo, Jiangsu, P. R. China) for 1 min (1 s, with 2-s interval) as described by Zhu et al (2015). Then, the homogenates were centrifuged at 1,000 × g for 15 min at 4°C to harvest the supernatants for immediately analyzing total protein content and CAT and SDH activities.…”
Section: Sample Collections and Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The birds were subsequently killed; samples of their liver, kidney, and heart were taken; and a subsample was frozen at −20°C for the analyses of Fe content and catalase (cAT) and succinate dehydrogenase (sDH) activities and another sample was frozen in liquid N for CAT and SDH gene expression assays. The samples of the liver, kidney, and heart were homogenized with a tissue grinder (T 18 D S25; IKA Group, Staufen, Germany) in ice-cold 10% (wt/vol) physiological saline for 1 min and then treated with an ultrasonic wave cell grinder (JY92-11; Ningbo Scientz Biotechnology Co., Ltd., Ningbo, Jiangsu, P. R. China) for 1 min (1 s, with 2-s interval) as described by Zhu et al (2015). Then, the homogenates were centrifuged at 1,000 × g for 15 min at 4°C to harvest the supernatants for immediately analyzing total protein content and CAT and SDH activities.…”
Section: Sample Collections and Preparationsmentioning
confidence: 99%
“…The primers for CAT, SDH, β-actin (housekeeping gene), and glyceraldehyde3phosphate dehydrogenase (GAPDH) gene (housekeeping gene) were chosen with Primer Express software (Applied Biosystems Inc., Foster, CA) and their information is summarized in Table 3. The β-actin and GAPDH genes were used to normalize the expressions of targeted genes CAT and SDH mRNA using the 2 −ΔΔCT method (Livak and Schmittgen, 2001;Zhu et al, 2015).…”
Section: Determinations Of the Activities Of Fe-containing Enzymes Inmentioning
confidence: 99%
“…To address the roles of the maternal dietary inorganic and organic Mn sources in the development of offspring embryos from the heat stressed broiler breeders as well as the deep mechanisms involved, the related data (see the captions in Figures 1 – 4 and Supplementary Figure 1 ) collected from chick embryos delivered from the control broiler breeders in our previous published study [ 31 ] were used for statistical analyses in the present study. The previous study [ 31 ] was conducted at the same time and facility as this study, and the broiler breeders raised at the normal temperature with a Mn-unsupplemented diet or the basal diet supplemented with the inorganic Mn were treated as the control maternal groups for the present study in accordance with the requirements of the Animal Welfare Committee of the Institute of Animal Science, Chinese Academy of Agricultural Sciences.…”
Section: Resultsmentioning
confidence: 99%
“…Yolk ( D ) and liver ( E ) Mn contents were measured based on fresh basis. The data of Mn contents in yolk and liver from the M-CON and M-iMn groups under M-NT as the control groups in the present study have been published in our previous study [ 31 ]. Based on the 2-way ANOVA analyses, “ * ” means significant differences at P < 0.05 between M-NT ( n = 18) and M-HT ( n = 18) as determined by a main effect of maternal environmental temperature; lacking common letters (a, b or c) means significant differences at P < 0.05 between grouped bars (maternal dietary Mn sources, n = 12) or between single bars (individual treatments, n = 6) as determined by a main effect of maternal dietary Mn or their interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Gallup and Norris (1939) reported that Mn deficiency in laying hens caused decreased hatchability and increased mortality of embryos. The recent study from our laboratory has demonstrated that maternal dietary supplementation with Mn could improve hatchability as well as antioxidant ability to protect offspring chick embryos against heat challenge during incubation from the 10th to 18th days of incubation (Zhu et al 2015b). Therefore, supplementation with Mn in laying hen diets can be an alternative way to protect cells from oxidative stress during the chick embryonic development.…”
Section: Itemmentioning
confidence: 99%